Portable Heating Lunch Box - Adan , Nor Faezah; Anak Micheal, Melvin Brian; Md Lajis, Lubna Nazihah; Abd Maulud, Maizatul qibria (Multidisciplinary Applied Research and Innovation, 2023)
Nowadays, there are still a small number of individuals who carry packed lunches for the lunch break. It’s strongly recommended to do this because there are a number of benefits to packing your own lunch from home that we are ignorant of. In comparison to food stands, home-cooked meals are of higher quality. However, most people who bring meals from home will face the problem of the food becoming cold at lunchtime. The major goal of this project is to design a portable lunch box that works to heat food based on a set temperature and time anywhere with a power supply and also to develop a food heating system with a notification to users. This paper proposes a lunch box that can be reheated where the PTC thermistor in this lunch box is used to heat foods. The lunch box can be operated manually by using buttons or via Bluetooth to the handphone for selections of time and temperature. The Bluetooth is connected to the handphone through the operation of Arduino Uno and Hc05. Users are able to set and monitor the time to heat the lunchbox on their smartphone when it is connected to the lunch box through bluetooth. By this, it eases user to heat their food and keeps them reminded. The temperature readings displayed on the LCD for each one-minute interval were recorded as the PTC heating element of the food container was heated from 0 to 11 minutes. According to the observations, the lowest temperature recorded was 27°C and the highest temperature reached 34°C.